PENDIDIKAN WANITA DALAM PERSFEKTIF FILSAFAT PENDIDIKAN ISLAM - Luciana Luciana (Universitas Muhammadiyah Tapanuli Selatan, 2019)
Abstract: Islam strongly encourages the education of women both in the religious and social fields. Cultural education and training are considered as an integral dimension of social development. There is no priority for men over women in relation to the right to education. Both of them were encouraged to get education, as already said, 'from the cradle to the grave'. Indeed, all the verses of the Qur'an that are related to education and those that advocate for the acquisition of knowledge are directed to both men and women. In accordance with the commands of the Koran and Hadiths encouraging women to develop all aspects of their personality, it is believed that an educated Muslim woman must not only emit moral qualities in her home environment, but she must also have an active role in the broad fields of social, economic development and politics. For how does a woman uphold good social and economic policies or disagree with them if she is not intellectually equipped for the task? Key Word: Pendidikan Wanita , Persfektif Filsafat